47m=18-27m

Combine 47 and m.

4m7=18-27m

Combine m and 27.

4m7=18-m⋅27

Move 2 to the left of m.

4m7=18-2m7

4m7=18-2m7

Add 2m7 to both sides of the equation.

4m7+2m7=18

Combine the numerators over the common denominator.

4m+2m7=18

Add 4m and 2m.

6m7=18

6m7=18

Multiply both sides of the equation by 76.

76⋅6m7=76⋅18

Simplify 76⋅6m7.

Cancel the common factor of 7.

Cancel the common factor.

76⋅6m7=76⋅18

Rewrite the expression.

16⋅(6m)=76⋅18

16⋅(6m)=76⋅18

Cancel the common factor of 6.

Factor 6 out of 6m.

16⋅(6(m))=76⋅18

Cancel the common factor.

16⋅(6m)=76⋅18

Rewrite the expression.

m=76⋅18

m=76⋅18

m=76⋅18

Simplify 76⋅18.

Cancel the common factor of 6.

Factor 6 out of 18.

m=76⋅(6(3))

Cancel the common factor.

m=76⋅(6⋅3)

Rewrite the expression.

m=7⋅3

m=7⋅3

Multiply 7 by 3.

m=21

m=21

m=21

Solve for m 4/7m=18-2/7m